2022
DOI: 10.1038/s41421-022-00390-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic O-GlcNAcylation coordinates ferritinophagy and mitophagy to activate ferroptosis

Abstract: Ferroptosis is a regulated iron-dependent cell death characterized by the accumulation of lipid peroxidation. A myriad of facets linking amino acid, lipid, redox, and iron metabolisms were found to drive or to suppress the execution of ferroptosis. However, how the cells decipher the diverse pro-ferroptotic stress to activate ferroptosis remains elusive. Here, we report that protein O-GlcNAcylation, the primary nutrient sensor of glucose flux, orchestrates both ferritinophagy and mitophagy for ferroptosis. Fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
77
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 65 publications
1
77
1
Order By: Relevance
“…Supported by this work and many other studies, triggering OGA activation for reduced O -GlcNAcylation may have potential therapeutic benefits by synergizing with other treatments. For example, reduction of O -GlcNAc through inhibiting OGT was recently reported to promote ferroptosis in U2OS cancer cells . Recent advances in mRNA delivery provide the opportunity to implement this selectively activatable OGA for assisting O -GlcNAc modulation in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supported by this work and many other studies, triggering OGA activation for reduced O -GlcNAcylation may have potential therapeutic benefits by synergizing with other treatments. For example, reduction of O -GlcNAc through inhibiting OGT was recently reported to promote ferroptosis in U2OS cancer cells . Recent advances in mRNA delivery provide the opportunity to implement this selectively activatable OGA for assisting O -GlcNAc modulation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…For example, reduction of O-GlcNAc through inhibiting OGT was recently reported to promote ferroptosis in U2OS cancer cells. 49 Recent advances in mRNA delivery 50 provide the opportunity to implement this selectively activatable OGA for assisting O-GlcNAc modulation in vivo. As findings about the modulation of O-GlcNAc and its spatiotemporal relationship to cellular processes are refined, the connection of O-GlcNAc to biological functions and eventually new therapeutic targets will increase in the future.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Ferroptosis was shown to be regulated by DElncRNA-enriched pathways, protein O-glycosylation as well as glutamine, glutamate and transferrin [ 121 , 122 , 123 , 124 ]. On the other hand, ferroptosis was previously shown to be influenced by DEPCG-enriched pathways, induced by glutathione peroxidase suppression (selenocysteine-containing enzyme) and SMG9 (a component of the NMD machinery) and inhibited by ceruloplasmin and Hedgehog pathway activation [ 125 , 126 , 127 , 128 , 129 , 130 , 131 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 47 ] In addition, resveratrol can enhance MB by activating sirtuin 1 to catalyze the deacetylation of PGC-1α, resulting in improved neurological function. [ 9 , 87 ] Studies have found that the expression of PGC-1α is reduced in rats after spinal cord injury, and lentivirus overexpression (PGC-1a) in neuronal cells effectively reduces neuronal cell death. [ 88 ] This suggests that the modulation of MB by increasing PGC-1α levels can potentially improve functional recovery after SCI.…”
Section: Mitochondrial-based Treatment Of Spinal Cord Injurymentioning
confidence: 99%